KUALITAS SITUS WEBSITE PEMERINTAHAN DAERAH KABUPATEN DI PULAU FLORES NUSA TENGGARA TIMUR - Delang, Teresa Ona; Munandar, Agus (Universitas Muhammadiyah Palembang, 2022)
This study aims to find the quality of district government websites on Flores Island, East Nusa Tenggara, namely the districts of Manggarai, West Manggarai, East Manggarai, East Flores, Ende, Nagekeo, Ngada and Sikka. This type of research uses descriptive - interpretive, namely research that describes, interprets and describes problems and makes decisions from the results of website quality. Documentation is a data collection method used in the form of website data from InfoASN.id using tools provided by Web Dev / Measure page quality. The results of this study indicate that the average for Performance is 57%. Accessibility 74% . Best Practices 69% which is included in the category of moderate quality. As for SEO, it is at the level of quality assessment with an average percentage of 92%